PERSPEKTIF KEADILAN DAN KEPASTIAN HUKUM DALAM PUTUSAN PRAPERADILAN NOMOR: 04/Pid.Prap/2015/PN.Jkt.Sel. TAHUN 2015 - Oktein Josephus Susak (Arena Hukum, 2016)
AbstractPretrial arrangement in the Criminal Procedure Code is a strict rule with a clear limitation. One function of pretrial is to test the validity of the initial arrest and detention as a forced effort on behalf of legislation. Pretrial in the formulation of the Criminal Procedure Code is more directed at administrative oversight. In a pretrial ruling No. 04/Pid.Prap/2015/PN.Jkt.Sel., judges have intruded normative boundaries by extending the authority of a preliminary hearing object includes examining â€œdetermination of the suspectâ€, although not explicitly mentioned in the Criminal Procedure Code provisions. The problem in this research is â€œHow is the existence of Criminal Pretrial Case Decision No. 04/Pid.Prap/2015/PN.Jkt.Sel., viewed from the aspect of justice and the rule of law?â€. This research is a normative juridical approach method using the conceptual approach, case approach and the approach of legislation. Based on the findings, it was concluded that the examination in pretrial is a voluntair examination as an effort to actualize the procedural justice, but related Â to a quo case, to realize substantial justice the judges act by entering the â€œdetermination of the suspectâ€ as an element of the object of new norms in the series Article 77 letter a Criminal Procedure Code into a pretrial authority. This creates legal uncertainty, since it contradicts with the principle of Lex Specialis Derogat Legi Generalis, Noscitur a Sociis principle, Ejusdem Generis principle and the principle of Expressio Unius Exclusio Alterius. With the model of reasoning methods argumentum a'contrario as one of the construction methods of the law against Article 77 letter a Criminal Code, it is known that the â€œdetermination of the suspectâ€ is not a pretrial object . The actions of judges had exceeded its authority, and the logic of the law of the judge in the formation of the new norm object element does not include extensive interpretation but a construction model law by analogy to the method of interpretation is contrary to the principle of legality and is not allowed in criminal law.Â AbstrakPengaturan praperadilan dalam KUHAP merupakan aturan yang ketat dengan limitatif yang jelas. Salah satu fungsi praperadilan adalah untuk menguji keabsahan proses awal penangkapan dan penahanan sebagai upaya paksa atas nama undang-undang. Praperadilan dalam rumusan KUHAP lebih mengarah pada pengawasan administratif. Dalam putusan Nomor : 04/Pid.Prap/2015/PN.Jkt.Sel., hakim telah menerobos batasan normatif dengan memperluas obyek kewenangan pemeriksaan praperadilan meliputi pemeriksaan â€œpenetapan tersangkaâ€, meskipun secara eksplisit ketentuannya tidak disebutkan dalam KUHAP.Permasalahan dalam penelitian ini adalah â€œBagaimana eksistensi Putusan Perkara Pidana Praperadilan Nomor : 04/Pid.Prap/ 2015/PN.Jkt.Sel.,Â ditinjau dari aspek keadilan dan kepastian hukum?â€. Penelitian ini merupakan penelitian yuridis normatif dengan metode pendekatan meliputi pendekatan konseptual, pendekatan kasus dan pendekatan perundang-undangan.Berdasarkan hasil penelitian, disimpulkan bahwa pemeriksaan dalam praperadilan merupakan pemeriksaan voluntair sebagai upaya mewujudkan keadilan prosedural, namun terkait perkara a quo, hakim seolah-olah hendak mewujudkan keadilan substansial dengan memasukkan â€œpenetapan tersangkaâ€ sebagai unsur objek norma baru dalam rangkaian Pasal 77 huruf a KUHAP menjadi kewenangan praperadilan. Hal ini menciptakan ketidakpastian hukum, karena bertentangan dengan asas Lex Specialis Derogat Legi Generalis, asas Noscitur a Sociis, asas Â Ejusdem Generis dan asas Expressio Unius Exclusio Alterius. Dengan model penalaran metode argumentum aâ€™contrario sebagai salah satu dari metode konstruksi hukum terhadap Pasal 77 huruf a KUHAP, diketahui bahwa â€œpenetapan tersangkaâ€ bukanlah obyek praperadilan. Tindakan hakim tersebut telah melampaui kewenangannya, dan logika hukum hakim dalam pembentukkan unsur objek norma baru tersebut tidak termasuk penafsiran ekstensif namun merupakan model konstruksi hukum dengan metode interpretasi analogi yang bertentangan dengan asas legalitas dan tidak diperbolehkan dalam hukum pidana.Â